The house where I live - Kudryavtsev, Alexander (project baikal, 2026)
Rental buildings of the early twentieth century are a significant segment of the development of large Russian cities. The skills of the architects and the convenience of living allowed them to go through the trials of the twentieth century and preserve the residential function, adapting to socio-economic requirements. They form a stable historical image of Russian cities. Apartmentbuildings are genetically linked to modern rental housing, which is a significant help in solving the housing problem in Russia, especially for young families, single people and the development of labor migration.
Keywords: rental building; urban development; residential architecture; rental type apartment buildings; architect’s skill